Evaluasi Safety In Design (SID) dalam Perencanaan Konseptual SMKK di Proyek Jembatan - Dwitama, Monica Filarita; Suraji, Akhmad; HG, Sabril Haris (Jurnal Talenta Sipil, 2025)
Indonesia remains one of the countries with the highest rates of construction accidents, with the main issues related to safety in construction projects, particularly during the design phase. Therefore, the role of design consultants is crucial in assessing safety risks throughout the design process, in accordance with the Guidelines of the Minister of Public Works Regulation No. 10 of 2021 on the Construction Safety Management System (CSMS). The research objective is to evaluate the understanding and challenges of Safety in Design (SID) practices in bridge planning projects. The study was validated using data triangulation techniques and analyzed using mixed methods. The results of the study indicate that the percentage of SMKK implementation in the Work Framework Document (KAK) for bridge project planning is 60% and 62% (good implementation), based on interviews with planning consultants, who reported an average SMKK implementation rate of 39,22% (poor implementation). Meanwhile, the questionnaire results on SMKK implementation have a percentage of 50,50% (poor implementation). The conclusion indicates that the level of understanding and practice of Safety in Design (SID) based on Ministerial Regulation No. 10 of 2021 on the Construction Safety Management System (SMKK) in bridge project planning in Indonesia has not been effectively implemented, as there are several barriers to applying the RK-SMKK in design.